2015
DOI: 10.1590/1982-0194201500045
|View full text |Cite
|
Sign up to set email alerts
|

Violência doméstica na gravidez

Abstract: Objective: To characterize domestic violence in pregnancy. Method: Cross-sectional, exploratory and analytical study of domestic violence with 385 women who attended a public maternity. The Chi-square test of Pearson and Fisher exact test were used to verify associations and considering significant results p<0.05. Data of the sociodemographic characteristics of women, partners and family members and items of "Abuse Assessment Screen-AAS" were collected. Results: Domestic violence compromised 36.9% of women at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0
16

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 17 publications
4
11
0
16
Order By: Relevance
“…The finding is consistent with that of study conducted among native Americans (52.5%) [26]. Our finding is significantly higher than those of studies conducted in Kisumu district hospital, Kenya (37%) [5], Rwanda(35.1%) [6], Sao Paulo, Brazil(34.6%) [8], KwaZulu-Natal, South Africa(31%) [7], Mulago Hospital, Uganda(27.7%) [17], Lima, Peru (45.1%) [27], Portuguese health institutions (43.4%) [28], Pakistan (51%) [29], Hull Maternity Hospital, UK (17%) [30]. It is also higher than that of a systematic review of African studies conducted between 2000 and 2010 and found that the prevalence of intimate partner violence ranged from 2 to 57% with an overall prevalence of 15.23% [31].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The finding is consistent with that of study conducted among native Americans (52.5%) [26]. Our finding is significantly higher than those of studies conducted in Kisumu district hospital, Kenya (37%) [5], Rwanda(35.1%) [6], Sao Paulo, Brazil(34.6%) [8], KwaZulu-Natal, South Africa(31%) [7], Mulago Hospital, Uganda(27.7%) [17], Lima, Peru (45.1%) [27], Portuguese health institutions (43.4%) [28], Pakistan (51%) [29], Hull Maternity Hospital, UK (17%) [30]. It is also higher than that of a systematic review of African studies conducted between 2000 and 2010 and found that the prevalence of intimate partner violence ranged from 2 to 57% with an overall prevalence of 15.23% [31].…”
Section: Discussionsupporting
confidence: 91%
“…The finding is consistent with those of studies conducted in Gondar [37], western Ethiopia [38], Awi zone, Ethiopia [34], Shimelba, Eritreans’ refugee camp, Ethiopia [39], Kisumu district hospital, Kenya [5], Rwanda [6], Sao Paulo, Brazil [8], the 9 countries of the WHO multi-country study, including Ethiopia [40]. This also was a determinant variable that increased the risk of domestic violence during pregnancy in the systematic reviews of 19 African journals(2000-2010GC) [31].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A cross-sectional study carried out with puerperal mothers in a public maternity hospital in São Paulo found that approximately 35% of the participants had been victims of some kind of violence during pregnancy. 2 In another study, approximately 16.0% of the pregnant women showed psychological victimization, 6.0% suffered physical violence and a lower percentage (1.3%) reported sexual violence during pregnancy. 3 It is important to mention that exposure to violence during pregnancy has been associated in the literature with a number of adverse maternal and fetal outcomes, 4 which may have serious consequences for the woman's health, fetus and also for the newborn, such as premature childbirth labor 5 and low birth weight (LBW).…”
Section: Introductionmentioning
confidence: 95%